That’s Vogue / Nur Nadiah Abd Halim and Nurul Nabihah Zahari - Abd Halim, Nur Nadiah; Zahari, Nurul Nabihah (2022)
Face masks will be likely be a must for a very long time. When its significance was highlighted last year, we were eager to pitch in with our own collection of mask chain, not just in the sake of fashion but also to promote where, who, and how people may stay safe. Without a question, the epidemic has significantly altered our lives. One of them is the required face masks, which are as essential to our appearance as our clothing. Nevertheless, while we adjust to this new norm, we occasionally forget to carry this new necessity. To complement this fundamental item of clothing, there has been a rush of innovations, such as mask chain. That’s Vogue shop is an online shop that sell a variety of design of mask chain. It was made to make it easier for users to use face masks especially for Hijabi with ear loop face mask. However, the mask chain not only simplifies but it makes the user look more attractive and stunning. We provide customer with a variety of design with a high quality and an affordable price. Furthermore, the functionality is also a key concern here, this multi-purpose chains can hold onto your masks, mask extender for hijabis and serve as lanyard or eyeglass chains. The customer can wear them on their own as beaded necklaces.